Radiological analysis and postoperative evaluation of multilocular ameloblastoma in young patient through panoramic radiograph: a case report - Rahman, Fadhlil UA.; Yunus, Barunawaty; Rasul, Irfan; Faisal, Faisal (Hasanuddin University, 2019)
Objective: Radiographic examination is the main supporting modality in helping to establish the diagnosis of lesion in the jaw.This paper aimed to describe how panoramic radiograph used to analyze the diagnosis and evaluate the results of treatment of ameloblastoma lesions.Methods: Panoramic radiographic examination was performed on an 18-year-old female patient with a chief complaint of swelling of the left mandible which caused the asymmetrical face. In addition to panoramic radiographs, CT scans were also added.Results: Radiograph panoramic showed a sizable well-defined multilocular radiolucency in left mandibular body area to the ramus extend to incisura of the mandible The lesion border had curved-corticated and scalloped border. The internal structure of the lesion was totally radiolucent with the presence of internal septa creating multilocular appearance. Effect the lesions on surrounding structures was destruction inferior cortical of mandible and root resorption. 3-dimensional CT scan was also performed and showed a pattern of lingual and buccal cortical involvement. Based on clinicoradiograph pattern this lesion was diagnosed as ameloblastoma.Conclusion: Panoramic radiographic examination is an important modality not only to help establish the diagnosis of ameloblastoma but also can be used to evaluate the results of lesion elimination by surgical intervention.Keywords: multilocular ameloblastoma, panoramic radiograph, postoperative evaluation